(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article delves into the multifaceted challenges faced in teaching English to preschool children, addressing diverse aspects such as individual learning styles, language interference, socioeconomic disparities, assessment methods, technological integration, and the importance of continuous research and adaptation. It explores innovative strategies and pedagogical approaches to overcome these challenges, ensuring effective language acquisition in early childhood education.